Relationship of vitamin D with the anthropometric indicators and lifestyle of adults. Medellín. Colombia - Giraldo Giraldo, Nubia Amparo; Ramírez Morales, Carolina; Idárraga Idárraga, Yelithza; Restrepo Moreno, Ángela; Cano Restrepo, Luz Elena; Mejía de los Ríos , Susana Pamela (Revista Cuidarte, 2023)
Highlights:• Vitamin D deficiency/insufficiency is a common problem in adults even in tropical countries• In this group of apparently healthy volunteers, vitamin D deficiency/insufficiency was very high.• Neither body mass index nor waist circumference was correlated with vitamin D status, although activities with increased sun exposure were highly correlated.• Although vitamin D deficiency/insufficiency does not constitute a disease per se, it is a risk factor for chronic diseases and therefore warrants care.Introduction: Serum vitamin D levels depend on sunlight, diet, and other factors. Objective: We aimed to determine serum vitamin D levels and evaluate their relationship with anthropometric indicators and lifestyle habits in apparently healthy volunteers. Materials and Methods: In this cross-sectional study (n=75), socio-demographic, anthropometric, and lifestyle habit-related data were collected. Serum vitamin D levels were determined with high performance liquid chromatography, food intake was measured by semiquantitative frequency and nutritional status was assessed by anthropometry. Chi-square test and also principal component analysis were used to analyze the relationship between some variables and vitamin D status. Spearman’s test was used to determine correlations between quantitative variables. Results: 73% were women and 61% belonged to medium socio-economic level. Median vitamin D intake was 137 (83.1–227.3) IU/day. Based on body mass index (BMI), 44% individuals had overweight/obesity. The 68% exhibited deficient/insufficient vitamin D levels (Hypovitaminosis D). BMI classification and waist circumference (CW) were not related with vitamin D status; however, activities with higher sun exposure were highly related (p = 0.013). Sun exposure time explained variation in component 2 (16.60%), where most of the individuals with normal level were grouped. Sun exposure time was positively correlated with vitamin D status (r = 0.263; p = 0.023). Discussion: Excess weight and abdominal obesity are not always associated with hypovitaminosis D. Conclusions: The majority of individuals showed hypovitaminosis D but their status was not related with anthropometric indicators. A Sun exposure time was the only factor positively correlated with vitamin D status. How to cite this article: Giraldo Giraldo Nubia Amparo, Ramírez Morales Carolina, Idárraga Idárraga Yelithza, Restrepo Moreno Ángela, Cano Restrepo Luz Elena, Mejía de los Rios Susana Pamela. Relationship of vitamin D with the anthropometric indicators and lifestyle of adults. Medellín. Colombia. Revista Cuidarte. 2023;14(3):e2920. http://dx.doi.org/10.15649/cuidarte.2920
Keywords: Vitamin D; Anthropometry; Life Style; Sunlight; Healthy Volunteers